Reconstructing cryptocurrency processes via Markov chains - Araújo, Tanya (2023)
The growing attention on cryptocurrencies has led to increasing research on digital stock markets. Approaches and tools usually applied to characterize standard stocks have been applied to the digital ones. Among these tools is the identification of processes of market fluctuations. Being interesting stochastic processes, the usual statistical methods are appropriate tools to their reconstruction. There, besides chance, the description of a behavioural component shall be present whenever a determinist pattern is ever found. Markov approaches are at the leading edge of this endeavour. In this paper, Markov chains of orders one to eight are considered as a way to forecast the dynamics of three major cryptocurrencies. It is accomplished using an empirical basis of intra-day returns. Besides forecasting, we investigate the existence of eventual long-memory components in each of those stochastic process. Results show that the average predictions obtained from using the empirical probabilities is better than random choices.